THE LEADERSHIP OF THE HEAD OF MADRASAH IN ESTABLISHING COMMUNICATION WITH STAKEHOLDER - Nadhirin, N (ADDIN, 2017)
Educational leadership in madrasah is one of education management functions. Madrasah is a formal religious education institution which provide educational services to the public. The quality of education in madrasah can be known one of them through the performance of madrasah leadership and vice versa. This research focused on madrasah leadership in building communication with stakeholder based on Sunnah Prophet Muhammad saw. This research uses qualitative approach with post-posivistic and phenomenology paradigm with multicase design. The findings empirically in communication the head of madrasah leadership in establishing communication with sakeholders is: (1) to establish cooperation relationship with stakeholders element; (2) silaturrahim structured activities; (3) into the motor changes madrasah progress; (4) spiritual orientation and social capital to achieve financial and human capital; (5) together work based on the principle of expediency; (6) taboo to discuss about salary and position and embarrassment show property and property ownership; (7) position is trust and not purpose; (8) firmly in giving sanction; (8) supervision of madrasah culture background; (9) time and work discipline; (10) build relationships with graduates through programmed activities.